Characterization of the complete mitochondrial genome of Coprinellus micaceus, a wild saprobic mushroom in China - Wang, Shu-rong (Mitochondrial DNA B Resour, 2021)
The Glistening Inkcap (Coprinellus micaceus) is a wild saprobic mushroom in China. In this study, we assembled and annotated its complete mitochondrial genome using raw data sequenced through Illumina NovaSeq 6000 platform (Illumina, San Diego, CA). The length of the C. micaceus mitochondrial genome is 65,450 bp with 33.05% GC content. Totally, 41 genes, including 14 protein-coding genes, 25 tRNAs and 2 rRNAs were identified in the mitochondrial genome. Phylogenetic analysis showed that the mitochondrial genome relationship between C. micaceus and Coprinopsis cinerea was the closest.